2019
DOI: 10.1111/sms.13435
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis biomarker responses and cartilage adaptation to exercise: A review of animal and human models

Abstract: Regular physical activity has been suggested as having both preventive and therapeutic benefits for individuals with osteoarthritis (OA). However, evidence of whether exercise and which type of exercise constitutes a benefit or a risk in the development and progression of OA remains debatable. This may be due to the evaluation of the effect of physical activity or new disease‐modifying OA drugs which is currently based on radiographic criteria (eg, joint space width) and the lack of correlation with clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 74 publications
(220 reference statements)
1
29
0
3
Order By: Relevance
“…Physical exercise plays a fundamental role in the prevention and treatment of several chronic diseases including OA [68]; and it is recommended by several guidelines as a first line intervention in the management of this condition [69][70][71]. Pathogenic mechanisms of the 'gut-joint axis' and the potential therapeutic role of physical exercise combined with diet and probiotics are depicted by Figure 1.…”
Section: Physical Exercise and Gut Microbiotamentioning
confidence: 99%
“…Physical exercise plays a fundamental role in the prevention and treatment of several chronic diseases including OA [68]; and it is recommended by several guidelines as a first line intervention in the management of this condition [69][70][71]. Pathogenic mechanisms of the 'gut-joint axis' and the potential therapeutic role of physical exercise combined with diet and probiotics are depicted by Figure 1.…”
Section: Physical Exercise and Gut Microbiotamentioning
confidence: 99%
“…There are currently no curative treatments for OA, resulting in heavy economic burden on patients, families, and society. Additionally, the molecular mechanisms of OA are unclear, and new and effective biomarkers are urgently needed to improve methods for the diagnosis and prevention of OA occurrence and progression [ 4 ]. Inflammatory mechanisms are important factors promoting the development of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity can prevent cartilage disorders and it has been suggested as a therapeutic tool for individuals with osteoarthritis (OA) [29]. Andersson et al reported that COMP serum levels increase after physical activity in OA patients [30].…”
Section: Discussionmentioning
confidence: 99%